ACI Update ACI News (Journal of Airport Management, 2019)
PURPOSE OF REVIEW: This review focuses on fecal microbiota transplantation (FMT) for urticaria via the gut skin axis, highlighting its timeliness and clinical relevance as an emerging strategy for refractory urticaria. RECENT FINDINGS: Recent studies confirm that gut microbiota dysbiosis drives urticaria pathogenesis via immune regulation and mast cell activation, with preliminary clinical data showing FMT can alleviate symptoms and restore gut barrier function. SUMMARY: FMT holds promise as a novel therapeutic option for urticaria, though further trials are needed to standardize protocols and confirm long-term safety for clinical translation.